Seaweed Research and Production in Kenya: Unveiling Opportunities and Current Research Gaps - Gladys Mwaka Holeh; Jan Mees; Jana Asselman; James Njiru; David Mirera; Colin Janssen; Ilias Semmouri (Reviews in Aquaculture, 2025)
This study reviews seaweed research activities and production in Kenya, serving as a case study to demonstrate the untapped potential and applicability in East Africa, especially in the context of the United Nations Sustainable Development Goals. Given the lack of consolidated scientific information and the fragmented nature of current seaweed farming efforts in Kenya, this review was undertaken to assess past and current research, identify production gaps, and offer direction for future development of a sustainable and competitive seaweed aquaculture industry in the region. In an extensive literature review, we identified 69 relevant manuscripts, primarily focusing on seaweed floristics and taxonomy, ecology, aquaculture and bioprospecting in the broadest meaning. Results reveal seaweed production was found to be minuscule compared to major global producers, despite a shifting research focus toward aquaculture in the last two decades. Seaweed farming faces environmental challenges such as unfavorable weather conditions and pathogen outbreaks, strongly impacting growth rates and production levels. The species currently commercially cultivated are used primarily for hydrocolloid extraction (carrageenans), explaining the limited interest in biochemical characterization of seaweed diversity, as most ‘bioprospecting’ studies focus on carrageenan and/or agar yields. With increasing investments into seaweed farming, concerns are rising regarding implications for the marine environment due to observed changes in sediment accumulation, changes in water quality, deforestation rates and shifts in marine biota. In conclusion, this study underscores seaweed's potential in Kenya, but also emphasizes the need for continued research and sustainable development practices to fully exploit this untapped resource.

The World Register of Marine Species (WoRMS) through the looking glass: insights from the data management team in light of the crystal anniversary of WoRMS - Leen Vandepitte; Stefanie Dekeyzer; Wim Decock; Lynn Delgat; Ben Boydens; Lennert Tyberghein; Bart Vanhoorne; Francisco Hernandez; Jan Mees; Tammy Horton; Andreas Kroh; Christopher B. Boyko; et al. (Hydrobiologia, 2025)
The World Register of Marine Species (WoRMS) started in 2007 with the question “how many species live in our oceans?”. Now, a little over 15 years later, WoRMS is able to answer several questions related to marine species discovery rates and provides a dynamic number of existing marine species, based on the information provided by hundreds of taxonomic experts worldwide, who have proven to be diverse and dynamic. We present basic statistics on marine species discovery rates based on the currently available content of WoRMS, as well as insights in the day-to-day activities and dynamics of our editorial board and the progress made so far on the content priorities as defined by the WoRMS Steering Committee. As for all dynamic systems, WoRMS is not complete and faces challenges. As an endorsed project of the UN Ocean Decade, WoRMS aims to tackle a number of these challenges and knowledge-gaps by 2030, including detailed documentation of authorships and original descriptions, and will provide continuous support to all marine initiatives, programs and projects that rely on WoRMS as an authoritative classification and catalogue of marine names.

Decadal decline of dominant copepod species in the North Sea is associated with ocean warming: Importance of marine heatwaves - Ilias Semmouri; Karel A.C. De Schamphelaere; Jonas Mortelmans; Jan Mees; Jana Asselman; Colin R. Janssen (Marine Pollution Bulletin, 2023)

Addressing data gaps in marine litter distribution: Citizen science observation of plastics in coastal ecosystems by high-school students - Ana I. Catarino; Edem Mahu; Marine I. Severin; Lazare Kouame Akpetou; Pavanee Annasawmy; Francis Emile Asuquo; Fiona Beckman; Mostapha Benomar; Annette Jaya-Ram; Mohammed Malouli; Jan Mees; Ivanice Monteiro; et al. (Frontiers in Marine Science, 2023)
The Citizen Observation of Local Litter in coastal ECosysTems (COLLECT) project (2021-2022) is a citizen science initiative, supported by the Partnership for Observation of the Global Ocean (POGO), which aimed to acquire distribution and abundance data of coastal plastic litter in seven countries: in Africa (Benin, Cabo Verde, Côte d’Ivoire, Ghana, Morocco, Nigeria) and Asia (Malaysia). In this paper, we describe the workflow used to establish and run this project, as well as the methodologies to acquire data. The COLLECT project consisted of training local students (15 - 18 years old) from ten second cycle institutions (“high schools”) on sampling and analyzing macro-, meso- and microplastics in beach sediments, using a quantitative assessment protocol. We further describe in detail the methodologies applied in assessing the impact of participating in the activities from a social sciences perspective. All documents and materials resulting from this project will be open access and available according to the FAIR Principles (Findable, Accessible, Interoperable, and Reusable). The results and outcomes from COLLECT will contribute to expanding knowledge and establishing baseline information on coastal plastic pollution, with citizen science being an enabler of open science, allowing data to be freely available to the public, academics and policymakers. Expected results from the use of the COLLECT protocol globally will further contribute to the identification of hotspots of coastal plastic litter, and bring awareness to local communities on the potential consequences of plastic pollution. The COLLECT project actively contributes with data suitable to survey plastic litter to the United Nations’ Sustainable Development Goals (UN SDGs), in particular to SDG 14, on the sustainable use of the ocean.

How Aphia—The Platform behind Several Online and Taxonomically Oriented Databases—Can Serve Both the Taxonomic Community and the Field of Biodiversity Informatics - Leen Vandepitte; Bart Vanhoorne; Wim Decock; Stefanie Dekeyzer; Aina Trias Verbeeck; Lorenzo Bovit; Francisco Hernandez; Jan Mees (Journal of Marine Science and Engineering, 2015)
The Aphia platform is an infrastructure designed to capture taxonomic and related data and information, and includes an online editing environment. The latter allows easy access to experts so they can update the content of the database in a timely fashion. Aphia is the core platform that underpins the World Register of Marine Species (WoRMS) and its more than 80 related global, regional and thematic species databases, but it also allows the storage of non-marine data. The content of Aphia can be consulted online, either by individual users or via machine-to-machine interactions. Aphia uses unique and stable identifiers for each available name in the database through the use of Life Science Identifiers (LSIDs). The system not only allows the storage of accepted and unaccepted names, but it also documents the relationships between names. This makes it a very powerful tool for taxonomic quality control, and also allows the linking of different pieces of information through scientific names, both within the Aphia platform and in relation to externally hosted databases. Through these LSIDs, Aphia has become an important player in the field of (marine) biodiversity informatics, allowing interactions between its own taxonomic data and e.g., biogeographic databases. Some applications in the field of biodiversity informatics encompass the coupling of species traits and taxonomy, as well as the creation of diverse, expert validated data products that can be used by policy makers, for example. Aphia also supplies (part of) its content to other data integrators and the infrastructure can be used to host orphan databases in danger of being lost.

Visions for the North Sea: The Societal Dilemma Behind Specifying Good Environmental Status - Alison J. Gilbert; Abigail McQuatters-Gollop; Olivia Langmead; Laurence Mee; Jan Vermaat (Ambio, 2015)

Marine Regions: Towards a Global Standard for Georeferenced Marine Names and Boundaries - Simon Claus; Nathalie De Hauwere; Bart Vanhoorne; Pieter Deckers; Francisco Souza Dias; Francisco Hernandez; Jan Mees (Marine Geodesy, 2014)

Archaeological charcoals as archives for firewood preferences and vegetation composition during the late Holocene in the southern Mayumbe, Democratic Republic of the Congo (DRC) - Wannes Hubau; Jan Van den Bulcke; Koen Bostoen; Bernard Olivier Clist; Alexandre Livingstone Smith; Nele Defoirdt; Florias Mees; Laurent Nsenga; Joris Van Acker; Hans Beeckman (Vegetation History and Archaeobotany, 2013)

Hundred and eighty years of fleet dynamics in the Belgian sea fisheries - Ann-Katrien Lescrauwaet; Nancy Fockedey; Heidi Debergh; Magda Vincx; Jan Mees (Reviews in Fish Biology and Fisheries, 2013)

Erratum to: Analysing the content of the European Ocean Biogeographic Information System (EurOBIS): available data, limitations, prospects and a look at the future - Leen Vandepitte; Francisco Hernandez; Simon Claus; Bart Vanhoorne; Nathalie De Hauwere; Klaas Deneudt; Ward Appeltans; Jan Mees (Hydrobiologia, 2011)

Analysing the content of the European Ocean Biogeographic Information System (EurOBIS): available data, limitations, prospects and a look at the future - Leen Vandepitte; Francisco Hernandez; Simon Claus; Bart Vanhoorne; Nathalie De Hauwere; Klaas Deneudt; Ward Appeltans; Jan Mees (Hydrobiologia, 2011)

Did global warming and alien invasions affect surf zone hyperbenthic communities on sandy beaches in Belgium? - Koen Lock; Jan Mees; Magda Vincx; Peter L. M. Goethals (Hydrobiologia, 2011)

Data integration for European marine biodiversity research: creating a database on benthos and plankton to study large-scale patterns and long-term changes - Leen Vandepitte; Bart Vanhoorne; Alexandra Kraberg; Natalie Anisimova; Chryssanthi Antoniadou; Rita Araújo; Inka Bartsch; Beatriz Beker; Lisandro Benedetti-Cecchi; Iacopo Bertocci; Sabine Cochrane; Keith Cooper; et al. (Hydrobiologia, 2010)

Changes in marsh nekton communities along the salinity gradient of the Schelde river, Belgium and The Netherlands - Henrietta Hampel; Andre Cattrijsse; Jan Mees (Hydrobiologia, 2004)

Additions to the mysid fauna (Crustacea: Mysidacea) from coastal waters of Mozambique, with descriptions of two new species - Tris Wooldridge; Jan Mees (Hydrobiologia, 2003)

Molecular characterization of a novel senescence-associated gene SPA15 induced during leaf senescence in sweet potato - Mee-Ngan Yap; Ruey-Hua Lee; Yih-Jong Huang; Chao-Jan Liao; Shu-Chen Grace Chen (Plant Molecular Biology, 2003)

Nematode communities of Lake Tana and other inland water bodies of Ethiopia - Eyualem Abebe; Jan Mees; August Coomans (Hydrobiologia, 2001)

Idiomysis mozambicus, a new mysid species (crustacea: mysidacea) from Mozambique - Tim Deprez; Tris Wooldridge; Jan Mees (Hydrobiologia, 2001)

A new species of Gastrosaccus (Crustacea, Mysidacea) from Algoa Bay (South Africa) - Tim Deprez; Tris Wooldridge; Jan Mees (Hydrobiologia, 2000)

Doxomysis algoaensis, a new mysid species (Crustacea: Mysidacea) from Algoa Bay (South Africa) - Tris Wooldridge; Jan Mees (Hydrobiologia, 2000)

A new species of Gastrosaccus (Crustacea, Mysidacea) from beaches in Madagascar - Tris Wooldridge; Jan Mees; Paul Webb (Hydrobiologia, 1997)

Aberrant individuals ofNeomysis integer and other Mysidacea: Intersexuality and variable telson morphology - Jan Mees; Nancy Fockedey; Ann Dewicke; Colin R. Janssen; Jean-Claude Sorbe (Aquatic Ecology, 1995)

Seasonal composition and spatial distribution of hyperbenthic communities along estuarine gradients in the Westerschelde - Jan Mees; Ann Dewicke; Olivier Hamerlynck (Aquatic Ecology, 1993)

The mobile epibenthic fauna of soft bottoms in the Dutch Delta (south-west Netherlands): Spatial structure - Olivier Hamerlynck; Kris Hostens; Renato V. Arellano; Jan Mees; Paul A. Damme (Aquatic Ecology, 1993)